International policy coordination and RMB internationalisation: theory and historical experience. Issue 1 (2nd January 2019) - Qian, Zongxin; Gan, Jingyun; Tu, Yonghong; Wang, Fang
Abstract: Based on theoretical logics derived from the literature and the historical experience, we take a deep look at the relationship between international policy coordination and RMB internationalisation. International policy coordination and RMB internationalisation are complements. On the one hand, an effective policy coordination mechanism needs the support of an efficient international monetary system, thus calling for diversification of international vehicle currencies. RMB, supported by solid economic fundamentals, can be a good candidate as one of the international vehicle currencies in the diversified international monetary system. On the other hand, due to the existence of policy spill-over effects, an appropriate coordination mechanism improves policy effectiveness in China, which promotes RMB internationalisation by enhancing China's economic and financial strength.